The application of the STAD cooperative learning model to improve Math learning outcomes - Desi Nur Rachmawati; Sandi Budi Iriawan; Haviz Kurniawan (Hipkin Journal of Educational Research, 2024)
This study aims to improve mathematics learning outcomes on diagram topics for second-grade students by applying the cooperative learning model, specifically the STAD (Student Teams Achievement Divisions) approach. Initial observations revealed that the teaching methods were ineffective, with low student participation and limited understanding of the material. This research employed a classroom action research approach with two cycles. In the first cycle, the implementation of the STAD model resulted in an average success rate of 63.39 percent, which was considered inadequate. In the second cycle, improvements were made by introducing more interactive and engaging teaching media. These improvements led to a significant increase in the success rate, reaching an average of 87.4 percent. The study demonstrates that applying the STAD model significantly enhanced students’ learning outcomes and engagement in the learning process. However, some students still required additional support to achieve mastery. This study highlights the importance of continuous evaluation and adaptation of teaching methods to meet individual student needs, ensuring that learning objectives are optimally achieved.   Abstrak Penelitian ini bertujuan untuk meningkatkan hasil belajar matematika pada materi diagram siswa kelas II melalui penerapan model pembelajaran kooperatif tipe STAD (Student Teams Achievement Divisions). Observasi awal menunjukkan bahwa metode pembelajaran yang digunakan kurang efektif, dengan partisipasi siswa yang rendah serta pemahaman yang terbatas terhadap materi. Penelitian ini menggunakan pendekatan tindakan kelas dengan dua siklus. Pada siklus pertama, penerapan model STAD menghasilkan rata-rata tingkat keberhasilan sebesar 63,39 persen, yang dianggap belum memadai. Pada siklus kedua, dilakukan perbaikan dengan memperkenalkan media pembelajaran yang lebih interaktif dan menarik. Hasil dari perbaikan ini menghasilkan peningkatan signifikan, dengan rata-rata tingkat keberhasilan mencapai 87,4 persen. Penelitian ini membuktikan bahwa penerapan model pembelajaran STAD secara signifikan mampu meningkatkan hasil belajar siswa serta keterlibatan mereka dalam proses pembelajaran. Meskipun demikian, terdapat beberapa siswa yang masih membutuhkan perhatian dan bimbingan tambahan untuk mencapai ketuntasan. Penelitian ini menekankan pentingnya melakukan evaluasi berkelanjutan dan menyesuaikan metode pembelajaran agar sesuai dengan kebutuhan individu siswa, sehingga tujuan pembelajaran dapat tercapai dengan optimal. Kata Kunci: pembelajaran kooperatif; hasil pembelajaran; matematika; STAD